PMO-089 Preoperative neutrophil: lymphocyte ratio is not a predictor of outcome following hepatic resection for colorectal metastases. (28th May 2012) - Western, C E; Wiggans, M; Aroori, S; Bowles, M; Stell, D
Abstract : Introduction: A high pre-operative neutrophil:lymphocyte ratio (NLR) has been shown in several studies to be associated with shorter disease-free and overall survival for a number of malignancies, including colorectal 1 and both primary 2 and secondary 3 liver tumours. This may reflect reduced lymphocyte function, so impaired host response or neutrophil-mediated angiogenesis enhancing tumour spread and has been proposed as a prognostic predictor. 1–3 We aimed to test this association by analysing pre-operative NLR in all patients undergoing liver resection for colorectal metastases (CRM) and attempting correlation with tumour recurrence, overall and disease-free survival. Methods: Our unit is a tertiary referral centre for both laparoscopic and open hepatic surgery. A prospectively collected database of demographic details, radiological and histological findings and blood test results has been maintained since July 2005 and this data has been retrospectively analysed to demonstrate potential associations with NLR. An NLR >5 was considered raised. Results: Between 15 July 2005 and 10 January 2012 247 hepatic resections were undertaken for CRM. Median age at surgery was 67 (range 33–91) and 64% were male. Overall median survival was 1818 days and overall median disease-free survival was 542 days. 125/247 (51%) CRM developed recurrent disease within the follow-up period. Follow-up ranged from 10 days to 5.9 years (median 20 months). 30 patients had a NLR >5. When Kaplan–Meier analysis was performed to compare median survival in those with a low vs a high NLR, it was seen that there was no significant difference between the two groups (p=0.81). There was also found to be no association between NLR and tumour recurrence (p=0.49) or time to recurrence (p=0.77). Conclusion: Contrary to previously published studies, our unit has not demonstrated an association between pre-operative NLR and tumour recurrence or survival in patients undergoing liver resection for CRM and suggests that this is not a useful prognostic indicator in this group of patients. Competing interests: None declared. References: 1. Hung HY, Chen JS, Yeh CY, et al. Effect of preoperative neutrophil–lymphocyte ratio on the surgical outcomes of stage II colon cancer patients who do not receive adjuvant chemotherapy. Int J Colorectal Dis 2011;26 :1059–65. 2. Gomez D, Farid S, Malik HZ, et al. Preoperative neutrophil-to-lymphocyte ratio as a prognostic predictor after curative resection for hepatocellular carcinoma. World J Surg 2008;32 :1757–62. 3. Halazun KJ, Aldoori A, Malik HZ, et al. Elevated preoperative neutrophil to lymphocyte ratio predicts survival following hepatic resection for colorectal liver metastases. Eur J Surg Oncol 2008;34 :55–60.